2017
DOI: 10.5301/ijbm.5000294
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio as Prognostic Indicator for Patients with Esophageal Squamous Cell Cancer

Abstract: Pretreatment NLR is independently associated with OS of ESCC patients. Therefore, NLR may be used as a predictive indicator for pretreatment evaluation and adjustment of treatment regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“… 16 , 20 , 22 , 24 26 All the included studies were carried out in Asia (15 studies in China, 10 studies in Japan, and only one study in Korea). The sample size of 16 studies was >200, 14 , 15 , 17 , 18 , 20 , 22 , 24 26 , 29 34 , 37 and the remaining 10 studies involved <200 patients. 16 , 19 , 21 , 23 , 27 , 28 , 35 , 36 , 38 , 39 Thirteen studies reported both survival and clinicopathological data, 15 , 16 , 20 , 22 26 , 31 34 , 37 and the other 13 studies only reported survival data.…”
Section: Resultsmentioning
confidence: 99%
“… 16 , 20 , 22 , 24 26 All the included studies were carried out in Asia (15 studies in China, 10 studies in Japan, and only one study in Korea). The sample size of 16 studies was >200, 14 , 15 , 17 , 18 , 20 , 22 , 24 26 , 29 34 , 37 and the remaining 10 studies involved <200 patients. 16 , 19 , 21 , 23 , 27 , 28 , 35 , 36 , 38 , 39 Thirteen studies reported both survival and clinicopathological data, 15 , 16 , 20 , 22 26 , 31 34 , 37 and the other 13 studies only reported survival data.…”
Section: Resultsmentioning
confidence: 99%
“…These biomarkers can be evaluated easily by sampling a small amount of peripheral blood. Prognostic significance has been gradually elucidated by accumulation of data from studies in gastrointestinal tumors such as esophageal cancer, gastric cancer, and colorectal cancer . However, few studies about the relationship between these biomarkers with respect to prognosis in patients with AEG have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic significance has been gradually elucidated by accumulation of data from studies in gastrointestinal tumors such as esophageal cancer, gastric cancer, and colorectal cancer. [17][18][19][20][21][22][23][24][25] However, few studies about the relationship between these biomarkers with respect to prognosis in patients with AEG have been published. In patients with AEG, pre-Alb, 33 body mass index, and NLR 34 were reported as independent prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations